Correlating Fluorescence and High-Resolution Scanning Electron Microscopy (HRSEM) for the study of GABAA receptor clustering induced by inhibitory synaptic plasticity. Issue 1 (December 2017) - Orlando, Marta; Ravasenga, Tiziana; Petrini, Enrica; Falqui, Andrea; Marotta, Roberto; Barberis, Andrea
Abstract Both excitatory and inhibitory synaptic contacts display activity dependent dynamic changes in their efficacy that are globally termed synaptic plasticity. Although the molecular mechanisms underlying glutamatergic synaptic plasticity have been extensively investigated and described, those responsible for inhibitory synaptic plasticity are only beginning to be unveiled. In this framework, the ultrastructural changes of the inhibitory synapses during plasticity have been poorly investigated. Here we combined confocal fluorescence microscopy (CFM) with high resolution scanning electron microscopy (HRSEM) to characterize the fine structural rearrangements of post-synaptic GABAA Receptors (GABAA Rs) at the nanometric scale during the induction of inhibitory long-term potentiation (iLTP). Additional electron tomography (ET) experiments on immunolabelled hippocampal neurons allowed the visualization of synaptic contacts and confirmed the reorganization of post-synaptic GABAA R clusters in response to chemical iLTP inducing protocol. Altogether, these approaches revealed that, following the induction of inhibitory synaptic potentiation, GABAA R clusters increase in size and number at the post-synaptic membrane with no other major structural changes of the pre- and post-synaptic elements.